Zastosowanie wybranych modeli tobitowych do opisu tygodniowej liczby godzin pracy - Kostrzewska, Jadwiga (An Application of Tobit Models to a Description of a Number of Hours Worked Per Week, 2008)
The aim of the paper is to present some types of tobit models and their application on the Polish labour market. There is made a trial of a description of a number of hours worked per week by married women in dependence on some characteristics which influence on being employed or unemployed. The results of an estimation of tobit models type I and II are compared with results of an estimation of classical regression models. The analysis is based on a data set from the labour force survey (BAEL) conducted by the CSO in Poland.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 128-135